Exceptional Children in Intermediate and Secondary Science Programs: A Teacher Survey. - Hoffman, Edward; West, Terry; Bates, Percy (Science Education)
The article reports on the direct contact and experience of intermediate and secondary science teachers with exceptional students in their classes in the U.S. Results show that majority of teachers had at least some exceptional students in their classes. However, no one type of exceptionality seemed to predominate. The two distinct clusters of exceptionality appeared to emerge from teachers' reports are: 1) students whose impairments were viewed as primarily academic-emotional; and, 2) those students whose impairments were seen as chiefly physical or sensory. The educable mentally impaired, emotionally impaired, and learning disabled were generally described as requiring fairly substantial modification of regular science teaching methods or materials.